Human mitotic spindles as active liquid crystals: From collective behaviors to discrete filaments - Suryanarayana Maddu; Colm P. Kelleher; Mustafa Basaran; Thomas Müller-Reichert; Michael J. Shelley; Daniel J. Needleman (Proceedings of the National Academy of Sciences, 2026)
How thousands of microtubules (MTs) and molecular motors self-organize into spindles remains poorly understood. By combining static, nanometer-resolution, large-scale electron tomography reconstructions and dynamic, optical-resolution, polarized light microscopy, we test an active liquid crystal continuum theory of mitotic spindles in human tissue culture cells. At micron length scales, probed by optical microscopy, the continuum theory accurately captures spindle morphology and fluctuation spectra, indicating that local interactions-polymerization, alignment, diffusion, and polar transport-govern the collective behaviors of MTs in human mitotic spindles. Electron tomography data enables tests of the continuum theory at submicron scales, revealing that chromosome-attached kinetochore microtubules (KMTs) show distinctive lateral organization not explained by the coarse-grained theory, while the non-KMTs that make up the bulk of the spindle follow the theory down to ∼300 nm length scales. At length scales below ∼300 nm, fluctuations arising from the intrinsic discreteness of the microtubule ensemble dominate over the collective correlations predicted from the continuum theory. Taken together, these findings show that an active liquid-crystal theory can quantitatively capture the self-organization of human mitotic spindles on long length scales and provides a means to measure the spindle’s material properties, while also pointing to the existence of additional processes contributing to the behaviors of KMTs.